Measuring Work Performance from Keyboard and Mouse Use - Dodi Wirawan Irawanto; Jusak Jusak; Noorsy Zidna Nabiela; Putri Oktaviani Syaiful (Politeknik Pertanian Negeri Samarinda, 2025)
In this modern and in age of industrial era 4.0 that was fostered by COVID-19 pandemic the challenge of increasing employee productivity is the main key to company success. One of the predictors of work performance for office workers are the use of computer aids such as keyboard and mouse. This study aims to explore how keyboard and mouse usage behavior affects work performance. The study shows that in the IoT era, poor predictability of work-related behavior from the use of computer accessories is encouraged. The sampling technique with accidental sampling, distributing 100 questionnaires to the target respondents giving the respond rates of 76% respondents using several survey techniques. The instruments use is developed from previous studies that prove to be effective in asking the perception of respondents. The data were analyzed using multiple linear regression, simple linear regression, and correlation through the Statistical Package for the Social Sciences (SPSS) version 27. The findings of this study revealed that keyboard usage behavior plays a significant and positive role in influencing work performance. In contrast, mouse usage behavior was not found to have a significant impact on work performance. This may be because some employees have other alternatives compared to using a mouse, namely a touchpad. Several recommendations for organization that employed office workers that mostly rely on computer for their work is posed to support work performance. This study is the bridging study to computer related study that can measures the productivity, and others work performance variables using more specific IoT tools such as sensors that enable to more accurate results better than perception study.